Plant source master batch, preparation method thereof and thermal polyamide fabric

By compounding cotton cellulose -based carbon particles with polyamide prefabrication, and reacting in a vacuum environment, the plant source mother particles with excellent and warm performance are prepared, and the problem of insufficient thermal warming performance of polyamide fiber is solved. The absorption and thermal performance of polyamide fabrics and the significant improvement of warmth performance.

CN119350843AInactive Publication Date: 2025-01-24DIJIU HIGH TECH MATERIALS (NANTONG) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411902459.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polyamide fiber has insufficient warm-keeping performance, single function and low added value, making it difficult to meet the market's demand for light and thin textiles with excellent warm-keeping performance.

Method used

Using plant-derived masterbatch, a polyamide fabric with excellent thermal insulation properties is prepared by compounding cotton cellulose-based carbon particles with polyamide prepolymer and reacting in a vacuum environment. The plant-derived masterbatch can also be combined with CNF/Fe3O4 to form a composite aerogel to further improve the thermal insulation performance of the fabric.

Benefits of technology

It has achieved a significant improvement in the light-absorbing, heat-generating and thermal insulation properties of polyamide fabrics, which can provide a longer-lasting thermal insulation effect while maintaining lightweight, and meet the market demand for high-performance textiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of functional polyamide master batches, in particular to a plant source master batch, a preparation method of the plant source master batch and a warm-keeping polyamide fabric. The plant source master batch is prepared by compounding a heat preservation modifier and a polyamide prepolymer according to a mass ratio of (30-40): 100, and the heat preservation modifier contains cotton cellulose-based carbon particles. The warm-keeping polyamide fabric can absorb light and emit heat, and meanwhile has an excellent warm-keeping effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional polyamide masterbatch, and more specifically, to a plant-based masterbatch and a preparation method thereof and a thermal insulation polyamide fabric. Background Art

[0002] With the continuous development of science and technology, synthetic fibers, as important textile raw materials, have been widely used in clothing, home furnishings, industrial textiles and other fields. Polyamide fiber, as a thin, soft and wear-resistant synthetic fiber, has been widely used in the textile field. However, the existing polyamide fibers have the defects of single function and low added value. Therefore, functional treatment of polyamide fibers is one of the main development directions of the current polyamide fiber industry.

[0003] Specifically, as a textile for clothing, heat preservation is one of its basic functions. Traditional thick and bulky thermal insulation textiles are gradually unable to meet people's needs. People hope that textiles have the advantages of both light texture and excellent thermal insulation performance. In summary, there is an urgent need for a polyamide fabric with light texture and excellent thermal insulation performance to expand the market. Summary of the invention

[0004] In order to improve the defect of insufficient thermal insulation performance of conventional polyamide fibers, the present application provides a plant-based masterbatch and a preparation method thereof and a thermal insulation polyamide fabric.

[0005] In the first aspect, the present application provides a plant-based masterbatch, which adopts the following technical solution: A plant-based masterbatch is obtained by compounding a thermal insulation modifier and a polyamide prepolymer in a mass ratio of (30-40):100, wherein the thermal insulation modifier contains cotton cellulose-based carbon particles.

[0006] Photothermal materials can absorb solar energy and generate heat. When applied to textiles, the textiles can also maintain their lightweight advantages. At present, common photothermal materials mainly include plasma materials such as gold, silver, aluminum, and copper; semiconductor materials such as titanium dioxide and molybdenum disulfide; and carbon-based materials such as graphene, carbon nanotubes, and activated carbon.

[0007] Among them, although plasma materials have excellent light absorption properties and photothermal conversion capabilities, they usually require effective morphology adjustment to overcome their inherent shortcomings of narrow absorption bandwidth, and they are expensive, which leads to certain limitations in practical applications.

[0008] Semiconductor materials are a type of photothermal material with development prospects, but most semiconductor oxides have a wide band gap and can only respond in the ultraviolet region, while ultraviolet light only accounts for 4% of sunlight, resulting in low utilization of the full spectrum of solar energy and limited application range.

[0009] Compared with other photothermal materials, carbon-based materials are low-cost, widely available, and have higher absorption efficiency and a wider excitation wavelength range for sunlight. Therefore, carbon-based materials are extremely suitable for use in the field of thermal insulation clothing. Cotton cellulose-based carbon particles are made from cotton fibers, activated by citric acid, ammonium polyphosphate, phosphoric acid or sulfuric acid, and finally carbonized. Cotton cellulose-based carbon particles have higher absorption efficiency and a wider excitation wavelength range for sunlight, thereby achieving extremely good light absorption and heating effects, which in turn promotes polyamide fabrics with plant-based masterbatches to have better thermal insulation properties.

[0010] Preferably, the method for preparing the cotton cellulose-based carbon particles comprises the following steps: S1. First, pretreat cotton fibers with a sodium carbonate solution having a mass fraction of 5% at 90-100° C. for 20-40 minutes, wash and dry them for later use, and obtain pretreated cotton fibers; S2, soaking the pretreated cotton fiber in an activator aqueous solution with a mass fraction of 10%, with a bath ratio of 1:19, heating it in a water bath at a temperature of 90-100° C. for 4-8 hours, and then drying it at a temperature of 100-110° C. for 2-4 hours, and finally adding deionized water to control the moisture content of the cotton fiber to 60%, thereby obtaining cotton fiber to be processed; S3. The cotton fibers to be processed are transferred to a furnace and carbonized at 350-450° C. for 10-30 min. The carbonized products are washed with deionized water until neutral and dried at 50-70° C. to obtain cotton cellulose-based carbon particles.

[0011] Preferably, the activator is one of citric acid, ammonium polyphosphate and sulfuric acid.

[0012] Preferably, the activating agent is sulfuric acid.

[0013] Among the above activators, the surface of carbon particles activated by citric acid is smoother than that of other carbon particles, which may be because citric acid has a cross-linking effect on cotton fibers. There are a certain amount of small particles on the surface of carbon particles activated by ammonium polyphosphate and phosphoric acid, which may be the decomposition products of the activators at high temperatures. The degree of fragmentation of carbon particles activated by sulfuric acid is the highest and the surface is porous, which may be because sulfuric acid can provide a large amount of H+, which attacks the hydrogen bonds between cellulose molecules, breaking the hydrogen bonds, and then H+ attacks the glycosidic bonds on the molecular chain, making the fibers The cellulose molecular chains are broken and cellulose is hydrolyzed.

[0014] On the other hand, due to the presence of sulfuric acid, the groups react with some hydroxyl groups on the cellulose molecular chain to form hydrogen sulfate esters, which reduces the strength of hydrogen bonds and accelerates the hydrolysis of cellulose into smaller molecules, thereby enabling more complete carbonization in the later stage.

[0015] The differences in the above-mentioned surface properties result in different light absorption and heat generation properties of the prepared cotton cellulose-based carbon particles, which are, from best to worst, sulfuric acid activation, ammonium polyphosphate activation, and citric acid activation.

[0016] Preferably, the thermal insulation modifier is CNF / Fe3O4@cotton cellulose-based carbon particle composite aerogel.

[0017] Although cotton cellulose-based carbon particles can provide polyamide fabrics with light-absorbing and heat-generating effects, the polyamide fabrics themselves have poor thermal insulation effects, which leads to insufficient sustainability of the heat generated by the cotton cellulose-based carbon particles, making it difficult to maintain long-term temperature.

[0018] When cotton cellulose-based carbon particles are combined with CNF / Fe3O4 to form composite aerogel, the thermal conductivity of aerogel is low, so it can significantly improve the thermal insulation performance of polyamide fabrics. In addition, there are a large number of air gaps inside the aerogel, which also have excellent thermal insulation properties, thus effectively reducing the heat transfer in the fabric. In addition, the density of aerogel is low, so it will not cause the polyamide mask to become bloated.

[0019] Preferably, the preparation method of the thermal insulation modifier comprises the following steps: Preparation of Fe3O4@cotton cellulose-based carbon microparticles: First, the cotton cellulose-based carbon particles were ground to 400-600 nm, and then 0.4-0.6 g of cotton cellulose-based carbon particles were dispersed in 150-250 ml of deionized water, and ultrasonicated for 20-40 min, and then 2-4 g of FeCl3·6H2O and 1-3 g of FeCl2·4H2O were added, dispersed and stirred for 20-40 min, and then 15-25 ml of ammonia water was added dropwise, stirred for 1 h, and finally dried at 40-60 ° C to obtain Fe3O4@cotton cellulose-based carbon particles; Preparation of CNF / Fe3O4@cotton cellulose-based carbon microparticle composite aerogel: The silane monomer and HCl were mixed in a mass ratio of 1:1, stirred for 10-20 minutes, and then fully dehydrated and condensed to obtain a polysilanized additive; at the same time, 40-60g of CNF suspension was adjusted to a concentration of 0.8wt%, and then mixed and dispersed evenly with 1-1.4g of Fe3O4@cotton cellulose-based carbon particles, the dispersion time was 20-40min, and the dispersion speed was 700-900r / min, and then 2-3v / v% of HCl / polysilanized additive solution was added, and mixing and dispersing were continued, the dispersion time was 6-10h, and the dispersion speed was 700-900r / min. After the modification was completed, the product was placed in a liquid nitrogen environment for freeze molding, and then the molded sample was placed in a dryer with a drying temperature of -48°C, a vacuum degree of 1Pa, and a drying time of 72h, and then placed in a 120°C environment for 2h to fully evaporate the water to obtain a CNF / Fe3O4@cotton cellulose-based carbon particle composite aerogel.

[0020] Preferably, the silane monomer is methyltrimethoxysilane or (2-mercaptoethyl)triethoxysilane.

[0021] Preferably, the silane monomer is (2-mercaptoethyl)triethoxysilane.

[0022] Compared with the use of methyltrimethoxysilane as the silane monomer, (2-mercaptoethyl)triethoxysilane contains mercapto groups. It may be because the mercapto groups can form hydrogen bonds with polyamide prepolymers, thereby further improving the compatibility of polyamide prepolymers and thermal insulation modifiers, and promoting polyamide fabrics to exhibit better light absorption and heat generation properties and thermal insulation properties.

[0023] Preferably, the preparation method of the polyamide prepolymer is: First, caprolactam, azelaic acid and deionized water are mixed in a mass ratio of 100: (12-18): (3-6), and then nitrogen is introduced and reacted while stirring. The reaction temperature is 230-280°C, the reaction pressure is 0.5-0.8Mpa, and the reaction time is 2-4h. The temperature is then reduced to room temperature and pressure, and the vacuum reaction is performed again for 2-4h. Finally, the temperature is restored to room temperature and pressure to discharge the material to obtain a polyamide prepolymer.

[0024] In a second aspect, the present application provides a method for preparing a plant-based masterbatch, using the following technical solution: A method for preparing a plant-based masterbatch comprises the following steps: firstly, mixing a polyamide prepolymer with a thermal insulation modifier, then reacting the mixture under vacuum at a temperature of 250-280° C. for 2-4 hours, and finally returning the mixture to normal temperature and pressure, discharging the mixture and pelletizing the mixture to obtain a plant-based masterbatch.

[0025] In a third aspect, the present application provides a thermal insulation polyamide fabric, which adopts the following technical solution: A warm polyamide fabric obtained by spinning and interweaving the above plant-derived masterbatch; The preparation method of the thermal insulation polyamide fabric comprises the following steps: Preparation of thermal insulation polyamide fiber: First, the plant-based masterbatch is added to a screw extruder, heated to 270-280°C, melted to form a melt and spun, the spinneret aperture is 0.65mm, the spinning speed is 2000m / min, and then the filament product is stretched and rolled, the stretching temperature is 90-110°C, the stretching multiple is 10 times, and then air-cooled, the air-cooling temperature is 20-30°C, the wind speed is 0.6m / s, and the relative humidity is 70%. After being wound into a roll, a thermal insulation polyamide fiber is obtained; Warm polyamide fabric preparation: Thermal insulation polyamide fiber is used as raw material, twisted into yarn, with a warp density of 33.8tex and a weft density of 42.4tex. Finally, it is plain woven through a knitting machine to obtain a thermal insulation polyamide fabric with a warp density of 93 strands / inch and a weft density of 82 strands / inch.

[0026] In summary, this application has the following beneficial effects: 1. Photothermal materials can absorb solar energy and generate heat. When applied to textiles, the textiles can also maintain their lightweight advantages. At present, common photothermal materials mainly include plasma materials such as gold, silver, aluminum, and copper; semiconductor materials such as titanium dioxide and molybdenum disulfide; and carbon-based materials such as graphene, carbon nanotubes, and activated carbon. Compared with other photothermal materials, carbon-based materials have low cost, wide sources, higher absorption efficiency and wider excitation wavelength range for sunlight. Therefore, carbon-based materials are extremely suitable for use in the field of thermal insulation clothing. Cotton cellulose-based carbon particles are made from cotton fibers, activated by citric acid, ammonium polyphosphate, phosphoric acid or sulfuric acid, and finally carbonized. Cotton cellulose-based carbon particles have higher absorption efficiency and wider excitation wavelength range for sunlight, thereby obtaining extremely excellent light absorption and heat generation effects, thereby enabling polyamide fabrics added with plant-based masterbatches to have better thermal insulation properties.

[0027] 2. Although cotton cellulose-based carbon particles can provide polyamide fabrics with the effect of absorbing light and generating heat, the polyamide fabric itself has poor thermal insulation effect, which leads to insufficient continuity of the heat generated by cotton cellulose-based carbon particles, making it difficult to maintain long-term temperature; When cotton cellulose-based carbon particles are combined with CNF / Fe3O4 to form a composite aerogel, the aerogel has low thermal conductivity, so it can significantly improve the thermal insulation performance of the polyamide fabric. There are also a large number of air gaps inside the aerogel, and the air gaps also have excellent thermal insulation properties, which can effectively reduce the heat transfer in the fabric. In addition, the density of the aerogel is low, so it will not cause the polyamide mask to become bloated.

[0028] 3. Compared with the use of methyltrimethoxysilane as the silane monomer, (2-mercaptoethyl)triethoxysilane contains mercapto groups. It may be because the mercapto groups can form hydrogen bonds with polyamide prepolymers, thereby further improving the compatibility of polyamide prepolymers and thermal insulation modifiers, and promoting polyamide fabrics to exhibit better light absorption and heat generation properties and thermal insulation properties. DETAILED DESCRIPTION

[0029] The present application is further described in detail below in conjunction with Examples 1-5 and Comparative Example 1.

[0030] raw material:

[0031] Sodium carbonate CAS: 497-19-8; cotton fiber is commercially available; citric acid CAS: 77-92-9; ammonium polyphosphate CAS: 68333-79-9; sulfuric acid CAS: 7664-93-9; FeCl3·6H2O CAS: 10025-77-1; FeCl2·4H2O CAS: 13478-10-9; ammonia CAS: 1336-21-6; HCl CAS: 2368870-94-2; CNF 1.60wt%, diameter 10-20 nm, length 10-20μm, Tianjin Muling Biotechnology Co., Ltd.; methyltrimethoxysilane CAS: 1185-55-3; (2-mercaptoethyl)triethoxysilane CAS: 18236-15-2; caprolactam CAS: 105-60-2; azelaic acid CAS: 123-99-9. Example 1

[0032] A plant-based masterbatch is obtained by compounding a thermal insulation modifier and a polyamide prepolymer in a mass ratio of 35:100. The preparation method is as follows: firstly, the polyamide prepolymer and the thermal insulation modifier are mixed, and then reacted in a vacuum environment at a reaction temperature of 270°C and a reaction time of 3 hours, and finally restored to normal temperature and pressure and discharged and pelletized to obtain the plant-based masterbatch.

[0033] The thermal modifier is cotton cellulose-based carbon microparticles; The method for preparing cotton cellulose-based carbon particles comprises the following steps: S1. First, pretreat cotton fibers with a sodium carbonate solution having a mass fraction of 5% at 100° C. for 30 minutes, wash and dry them for later use, and obtain pretreated cotton fibers; S2, soaking the pretreated cotton fiber in an activator aqueous solution with a mass fraction of 10%, with a bath ratio of 1:19, heating it in a water bath at a temperature of 100° C. for 6 hours, and then drying it at a temperature of 110° C. for 3 hours, and finally adding deionized water to control the moisture content of the cotton fiber at 60%, thereby obtaining the cotton fiber to be processed; Wherein, the activator is citric acid; S3. The cotton fibers to be processed are transferred to a Mafui furnace and carbonized at 400° C. for 20 min. The carbonized products are washed with deionized water until neutral and dried at 60° C. to obtain cotton cellulose-based carbon particles.

[0034] The preparation method of polyamide prepolymer is: First, undecanoic acid, azelaic acid and deionized water are mixed in a mass ratio of 100:16:5, and then nitrogen is introduced and reacted with stirring. The reaction temperature is 250°C, the reaction pressure is 0.7 MPa, and the reaction time is 3 hours. The temperature is then reduced to room temperature and pressure, and the vacuum reaction is performed again for 3 hours. Finally, the temperature is restored to room temperature and pressure to discharge the material to obtain a polyamide prepolymer.

[0035] A warm polyamide fabric obtained by spinning and interweaving the above plant-derived masterbatch; The preparation method of the thermal insulation polyamide fabric comprises the following steps: Preparation of thermal insulation polyamide fiber: First, the plant-based masterbatch is added to a screw extruder, heated to 280°C, melted to form a melt and spun, the spinneret aperture is 0.65mm, the spinning speed is 2000m / min, and then the filament product is stretched and rolled, the stretching temperature is 100°C, the stretching multiple is 10 times, and then air-cooled, the air-cooling temperature is 25°C, the wind speed is 0.6m / s, and the relative humidity is 70%. After being wound into a roll, the thermal insulation polyamide fiber is obtained; Warm polyamide fabric preparation: Thermal insulation polyamide fiber is used as raw material, twisted into yarn, with a warp density of 33.8tex and a weft density of 42.4tex. Finally, it is plain woven through a knitting machine to obtain a thermal insulation polyamide fabric with a warp density of 93 strands / inch and a weft density of 82 strands / inch. Example 2

[0036] The difference from Example 1 is that the activator is ammonium polyphosphate. Example 3

[0037] The difference from Example 1 is that the activator is sulfuric acid. Example 4

[0038] The difference from Example 3 is that the thermal insulation modifier is CNF / Fe3O4@cotton cellulose-based carbon microparticle composite aerogel; The preparation method of the thermal insulation modifier comprises the following steps: Preparation of Fe3O4@cotton cellulose-based carbon microparticles: First, the cotton cellulose-based carbon particles were ground to 500 nm, and then 0.5 g of cotton cellulose-based carbon particles were dispersed in 200 ml of deionized water, ultrasonicated for 30 min, and then 3 g of FeCl3·6H2O and 2 g of FeCl2·4H2O were added, dispersed and stirred for 30 min, and then 20 ml of ammonia water was added dropwise, stirred for 1 h, and finally dried at 50 ° C to obtain Fe3O4@cotton cellulose-based carbon particles; Preparation of CNF / Fe3O4@cotton cellulose-based carbon microparticle composite aerogel: Silane monomer and HCl were mixed in a mass ratio of 1:1, stirred for 15 minutes, and then fully dehydrated and condensed to obtain a polysilanized additive; at the same time, 50g of CNF suspension was adjusted to a concentration of 0.8wt%, and then mixed and dispersed evenly with 1.2g of Fe3O4@cotton cellulose-based carbon particles, with a dispersion time of 30 minutes and a dispersion speed of 700-900r / min, and then 3v / v% of HCl / polysilanized additive solution was added, and mixing and dispersion were continued, with a dispersion time of 8h and a dispersion speed of 800r / min. After the modification was completed, the product was placed in a liquid nitrogen environment for freeze molding, and then the molded sample was placed in a dryer with a drying temperature of -48°C, a vacuum degree of 1Pa, and a drying time of 72h, and then placed in a 120°C environment for 2h to fully evaporate the water to obtain a CNF / Fe3O4@cotton cellulose-based carbon particle composite aerogel; Wherein, the silane monomer is methyltrimethoxysilane. Example 5

[0039] The difference from Example 4 is that the silane monomer is (2-mercaptoethyl)triethoxysilane.

[0040] Comparative Example 1 The difference from Example 1 is that no thermal insulation modifier is added.

[0041] Performance testing Detection Methods

[0042] Light absorption and heating performance test Three samples were taken from Examples 1-3 and Comparative Example 1 respectively. All samples were irradiated under a 275W xenon lamp light source for 10 minutes at a standard temperature of 20°C. The temperature rise values ​​were then recorded and the average value was taken.

[0043] The test data are shown in Table 1.

[0044] Table 1 Light absorption and heat generation performance of Examples 1-3 and Comparative Example 1

[0045] Thermal insulation performance test Three samples were taken from Examples 3-5 respectively, and then all samples were placed under a 275W xenon lamp light source for 10 minutes at a standard environment of 20°C, and the instantaneous temperature was recorded. After that, they were left to stand at a standard environment of 20°C for 1 hour, and the temperature was measured again and the temperature drop value was calculated, and finally the average value was taken.

[0046] The test data are shown in Table 2.

[0047] Table 2 Thermal insulation performance of Examples 3-5

[0048] Referring to Examples 1-3 and Comparative Example 1 and in combination with Table 1, it can be seen that relative to Comparative Example 1, the temperature rise values ​​of Examples 1-3 are significantly improved, which indicates that the addition of thermal insulation modifier can effectively improve the light absorption and heat generation performance of polyamide fabrics.

[0049] The reason is that photothermal materials can absorb solar energy and generate heat, and when applied to textiles, the textiles can maintain their lightweight advantages. At present, common photothermal materials mainly include plasma materials such as gold, silver, aluminum, and copper; semiconductor materials such as titanium dioxide and molybdenum disulfide; and carbon-based materials such as graphene, carbon nanotubes, and activated carbon.

[0050] Among them, although plasma materials have excellent light absorption properties and photothermal conversion capabilities, they usually require effective morphology adjustment to overcome their inherent shortcomings of narrow absorption bandwidth, and they are expensive, which leads to certain limitations in practical applications.

[0051] Semiconductor materials are a type of photothermal material with development prospects, but most semiconductor oxides have a wide band gap and can only respond in the ultraviolet region, while ultraviolet light only accounts for 4% of sunlight, resulting in low utilization of the full spectrum of solar energy and limited application range.

[0052] Compared with other photothermal materials, carbon-based materials are low-cost, widely available, and have higher absorption efficiency and a wider excitation wavelength range for sunlight. Therefore, carbon-based materials are extremely suitable for use in the field of thermal insulation clothing. Cotton cellulose-based carbon particles are made from cotton fibers, activated by citric acid, ammonium polyphosphate, phosphoric acid or sulfuric acid, and finally carbonized. Cotton cellulose-based carbon particles have higher absorption efficiency and a wider excitation wavelength range for sunlight, thereby achieving extremely good light absorption and heating effects, which in turn promotes polyamide fabrics with plant-based masterbatches to have better thermal insulation properties.

[0053] Compared with Example 1, the temperature rise value of Example 2 is significantly improved, and the temperature rise value of Example 3 is further improved, which shows that the selection of the active agent can significantly improve the light absorption and heat generation performance of the polyamide fabric. Specifically, the light absorption and heat generation performance is from best to worst, sulfuric acid activation, ammonium polyphosphate activation, and citric acid activation.

[0054] The reason may be that the surface of citric acid activated carbon particles is smoother than that of other carbon particles, which may be because citric acid has a cross-linking effect on cotton fibers. There are a certain amount of small particles on the surface of carbon particles activated by ammonium polyphosphate and phosphoric acid, which may be the decomposition products of the activator at high temperature. The degree of fragmentation of sulfuric acid activated carbon particles is the highest and the surface is porous, which may be because sulfuric acid can provide a large amount of H+, which attacks the hydrogen bonds between cellulose molecules, breaking the hydrogen bonds, and then H+ attacks the glycosidic bonds on the molecular chain, breaking the cellulose molecular chain and hydrolyzing the cellulose.

[0055] On the other hand, due to the presence of sulfuric acid, the groups react with some hydroxyl groups on the cellulose molecular chain to form hydrogen sulfate esters, which reduces the strength of hydrogen bonds and accelerates the hydrolysis of cellulose into smaller molecules, thereby enabling more complete carbonization in the later stage.

[0056] Referring to Examples 3-4 and in combination with Table 2, it can be seen that the temperature drop value of Example 4 is significantly lower than that of Example 3, which shows that the use of CNF / Fe3O4@cotton cellulose-based carbon microparticle composite aerogel can effectively reduce heat loss, thereby effectively improving the thermal insulation performance of polyamide fabrics.

[0057] The reason is that although the cotton cellulose-based carbon particles can provide the polyamide fabric with the effect of absorbing light and generating heat, the polyamide fabric itself has poor thermal insulation effect, which leads to the insufficient continuity of the heat generated by the cotton cellulose-based carbon particles, making it difficult to maintain the temperature for a long time. When cotton cellulose-based carbon particles are combined with CNF / Fe3O4 to form a composite aerogel, the aerogel has low thermal conductivity, so it can significantly improve the thermal insulation performance of the polyamide fabric. There are also a large number of air gaps inside the aerogel, and the air gaps also have excellent thermal insulation properties, which can effectively reduce the heat transfer in the fabric. In addition, the density of the aerogel is low, so it will not cause the polyamide mask to become bloated.

[0058] Referring to Examples 4-5 and in combination with Table 2, it can be seen that, relative to Example 4, the temperature drop value of Example 5 is further reduced, which indicates that the selection of silane monomers can also affect the thermal insulation performance of polyamide fabrics. Specifically, relative to the selection of methyltrimethoxysilane, the selection of (2-mercaptoethyl)triethoxysilane can promote the polyamide fabric to have better thermal insulation performance.

[0059] The reason may be that (2-mercaptoethyl)triethoxysilane contains mercapto groups, which can form hydrogen bonds with polyamide prepolymers, thereby further improving the compatibility of polyamide prepolymers and thermal insulation modifiers, and enabling polyamide fabrics to exhibit better light absorption and heat generation properties and thermal insulation properties.

[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A plant-based masterbatch, characterized in that: The thermal insulation modifier is compounded with a polyamide prepolymer in a mass ratio of (30-40):100, wherein the thermal insulation modifier contains cotton cellulose-based carbon particles.

2. The plant-derived masterbatch according to claim 1, characterized in that: The method for preparing the cotton cellulose-based carbon particles comprises the following steps: S1. First, pretreat cotton fibers with a sodium carbonate solution having a mass fraction of 5% at 90-100° C. for 20-40 minutes, wash and dry them for later use, and obtain pretreated cotton fibers; S2, soaking the pretreated cotton fiber in an activator aqueous solution with a mass fraction of 10%, with a bath ratio of 1:19, heating it in a water bath at a temperature of 90-100° C. for 4-8 hours, and then drying it at a temperature of 100-110° C. for 2-4 hours, and finally adding deionized water to control the moisture content of the cotton fiber to 60%, thereby obtaining cotton fiber to be processed; S3. The cotton fibers to be processed are transferred to a furnace and carbonized at 350-450° C. for 10-30 min. The carbonized products are washed with deionized water until neutral and dried at 50-70° C. to obtain cotton cellulose-based carbon particles.

3. The plant-derived masterbatch according to claim 2, characterized in that: The activator is one of citric acid, ammonium polyphosphate and sulfuric acid.

4. The plant-derived masterbatch according to claim 1, characterized in that: The thermal insulation modifier is CNF / Fe3O4@cotton cellulose-based carbon particle composite aerogel.

5. The plant-derived masterbatch according to claim 4, characterized in that: The preparation method of the thermal insulation modifier comprises the following steps: Preparation of Fe3O4@cotton cellulose-based carbon microparticles: First, the cotton cellulose-based carbon particles were ground to 400-600 nm, and then 0.4-0.6 g of cotton cellulose-based carbon particles were dispersed in 150-250 ml of deionized water, and ultrasonicated for 20-40 min, and then 2-4 g of FeCl3·6H2O and 1-3 g of FeCl2·4H2O were added, dispersed and stirred for 20-40 min, and then 15-25 ml of ammonia water was added dropwise, stirred for 1 h, and finally dried at 40-60 ° C to obtain Fe3O4@cotton cellulose-based carbon particles; Preparation of CNF / Fe3O4@cotton cellulose-based carbon microparticle composite aerogel: The silane monomer and HCl were mixed in a mass ratio of 1:1, stirred for 10-20 minutes, and then fully dehydrated and condensed to obtain a polysilanized additive; at the same time, 40-60g of CNF suspension was adjusted to a concentration of 0.8wt%, and then mixed and dispersed evenly with 1-1.4g of Fe3O4@cotton cellulose-based carbon particles, the dispersion time was 20-40min, and the dispersion speed was 700-900r / min, and then 2-3v / v% of HCl / polysilanized additive solution was added, and mixing and dispersing were continued, the dispersion time was 6-10h, and the dispersion speed was 700-900r / min. After the modification was completed, the product was placed in a liquid nitrogen environment for freeze molding, and then the molded sample was placed in a dryer with a drying temperature of -48°C, a vacuum degree of 1Pa, and a drying time of 72h, and then placed in a 120°C environment for 2h to fully evaporate the water to obtain a CNF / Fe3O4@cotton cellulose-based carbon particle composite aerogel.

6. The plant-derived masterbatch according to claim 5, characterized in that: The silane monomer is methyltrimethoxysilane or (2-mercaptoethyl)triethoxysilane.

7. The plant-derived masterbatch according to claim 1, characterized in that: The preparation method of the polyamide prepolymer is: First, caprolactam, azelaic acid and deionized water are mixed in a mass ratio of 100: (12-18): (3-6), and then nitrogen is introduced and reacted while stirring. The reaction temperature is 230-280°C, the reaction pressure is 0.5-0.8Mpa, and the reaction time is 2-4h. The temperature is then reduced to room temperature and pressure, and the vacuum reaction is performed again for 2-4h. Finally, the temperature is restored to room temperature and pressure to discharge the material to obtain a polyamide prepolymer.

8. A method for preparing the plant-based masterbatch according to any one of claims 1 to 7, characterized in that: The steps are as follows: firstly, the polyamide prepolymer is mixed with the thermal insulation modifier, then the reaction is carried out in a vacuum environment, the reaction temperature is 250-280°C, the reaction time is 2-4h, and finally the temperature is restored to normal pressure and the material is discharged and pelletized to obtain a plant-based masterbatch.

9. A warm polyamide fabric, characterized in that: It is obtained by spinning and interweaving the plant-derived masterbatch described in any one of claims 1 to 7; The preparation method of the thermal insulation polyamide fabric comprises the following steps: Preparation of thermal insulation polyamide fiber: First, the plant-based masterbatch is added to a screw extruder, heated to 270-280°C, melted to form a melt and spun, the spinneret aperture is 0.65mm, the spinning speed is 2000m / min, and then the filament product is stretched and rolled, the stretching temperature is 90-110°C, the stretching multiple is 10 times, and then air-cooled, the air-cooling temperature is 20-30°C, the wind speed is 0.6m / s, and the relative humidity is 70%. After being wound into a roll, a thermal insulation polyamide fiber is obtained; Warm polyamide fabric preparation: Thermal insulation polyamide fiber is used as raw material, twisted into yarn, with a warp density of 33.8tex and a weft density of 42.4tex. Finally, it is plain woven through a knitting machine to obtain a thermal insulation polyamide fabric with a warp density of 93 strands / inch and a weft density of 82 strands / inch.

Citation Information

Patent Citations

  • Cold-proof and warm-keeping composite polyamide functional fiber, knitted fabric and preparation method of knitted fabric

    CN115044999A

  • Preparation method of photo-thermal conversion-heat storage temperature regulation thermal insulation fiber

    CN115341292A

  • Preparation method of thermal insulation fiber with photothermal conversion function

    CN115341297A

  • Light and wear-resistant polyamide fiber fabric

    CN118064996A